The answer is -52 so it would be C
Step-by-step explanation:
x(x-3)=0
x=0 or (x-3) =0
x= 0 or x =3
We have that an inverse variation in a function is given by:
We must find the value of the constant k.
To do this, we substitute the values of x1 = 12, y1 = 15.
We have then:
Clearing k we have:
Substituting the value of k we have that the inverse variation is:
For y2 = 3 we have:
Clearing x2 we have:
Answer:
<h3>
Answer: Choice D</h3>
Domain = [-3, infinity)
==================================================
Work Shown:
In step 2, we replaced every x with g(x)
In step 3, we plugged in g(x) = sqrt(x+3)
The domain of g(x) is [-3, infinity), so this is the domain of as well since the composite function depends entirely on g(x). Put another way: the input of f(x) depends on the output of g(x), so that's why the domains match up.
<span>Simplifying
7(2e + -1) + -3 = 6 + 6e
Reorder the terms:
7(-1 + 2e) + -3 = 6 + 6e
(-1 * 7 + 2e * 7) + -3 = 6 + 6e
(-7 + 14e) + -3 = 6 + 6e
Reorder the terms:
-7 + -3 + 14e = 6 + 6e
Combine like terms: -7 + -3 = -10
-10 + 14e = 6 + 6e
Solving
-10 + 14e = 6 + 6e
Solving for variable 'e'.
Move all terms containing e to the left, all other terms to the right.
Add '-6e' to each side of the equation.
-10 + 14e + -6e = 6 + 6e + -6e
Combine like terms: 14e + -6e = 8e
-10 + 8e = 6 + 6e + -6e
Combine like terms: 6e + -6e = 0
-10 + 8e = 6 + 0
-10 + 8e = 6
Add '10' to each side of the equation.
-10 + 10 + 8e = 6 + 10
Combine like terms: -10 + 10 = 0
0 + 8e = 6 + 10
8e = 6 + 10
Combine like terms: 6 + 10 = 16
8e = 16
Divide each side by '8'.
e = 2
Simplifying
<span>e=2
</span></span>
(sorry, i went into depth)